Global development of tourism through analysis of its participation in employment and GDP of Slovenia, Serbia and the European Union - Cvijanović, Drago V. (Revija za ekonomske in poslovne vede, 2021)
Tourism development is a global phenomenon. The growth of the number of employees in this industry, as well as its participation in the creation of the gross domestic product of all countries is a reality. That is why its study is a necessity for accelerating the development of economic policies by further measures. This paper will be based on identifying employment trends in the tourism industry, as well as its participation in the creation of the gross domestic product of Slovenia, Serbia and the rest of the European Union. A very important factor in the development of tourism and of the entire economy is capital investments, which will also be included in the analysis. For the sake of a complete consideration of all types of participation, we will also consider indirect participation, in addition to direct participation, as it is more dominant than direct participation as regards employment and gross domestic product.
Keywords: bruto domači proizvod; capital investment; employment; gross domestic product; kapitalska naložba; tourism; turizem; zaposlovanje